2021
DOI: 10.1186/s13287-021-02193-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anti-inflammatory effects of mesenchymal stromal cells mediated by the transient ectopic expression of CXCR4 and IL10

Abstract: Background Mesenchymal stromal cells (MSCs) constitute one of the cell types most frequently used in cell therapy. Although several studies have shown the efficacy of these cells to modulate inflammation in different animal models, the results obtained in human clinical trials have been more modest. Here, we aimed at improving the therapeutic properties of MSCs by inducing a transient expression of two molecules that could enhance two different properties of these cells. With the purpose of imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 62 publications
4
25
0
Order By: Relevance
“…HIF-1α overexpression in MSC is not the only modification that has been implemented to enhance MSC properties in different experimental scenarios. For instance, it has been shown that modification of MSC by overexpression of key molecules involved in homing and immunosuppression (as CXCR4 and IL10) or by exofucosylation can improve MSC properties [ 28 30 ]. Preconditioning of these cells with pro-inflammatory cytokines, irradiation, pharmacological or chemical agents may have similar effects [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α overexpression in MSC is not the only modification that has been implemented to enhance MSC properties in different experimental scenarios. For instance, it has been shown that modification of MSC by overexpression of key molecules involved in homing and immunosuppression (as CXCR4 and IL10) or by exofucosylation can improve MSC properties [ 28 30 ]. Preconditioning of these cells with pro-inflammatory cytokines, irradiation, pharmacological or chemical agents may have similar effects [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some reported functional improvements in different preclinical conditions, include transplantation 52 54 , myocardial infarction 55 , 56 , osteoporosis 57 , cerebral ischemia 58 , graft versus host disease (GVHD) 59 , acute lung injury 60 , diabetic retinopathy 61 , and colitis-associated tumorigenesis 62 models. In addition to stable overexpression of CXCR4, Hervás-Salcedo et al showed that mRNA-transfected MSCs also possess enhanced transient CXCR4 expression and increased migration towards SDF-1 in an LPS-induced inflamed mouse model 63 . Our results regarding the comparison of Wild-type CXCR4 overexpressing MSCs with unmanipulated MSCs are in line with their results.…”
Section: Discussionmentioning
confidence: 99%
“…Upon successful animal model studies, recent gene-editing methods could also be employed to accelerate the translational process, including AAV-mediated gene therapy, zinc finger nucleases (ZFNs), transcription activator-like effector nucleases (TALENs), and clustered interspaced short palindromic repeats (CRISPR) in combination with CRISPR-associated protein (Cas) 70 . Another considerable strategy to facilitate the clinical application could be transiently expressing Mutant CXCR4 , using other safer approaches such as in vitro transcription 63 . As a prominent cell-free method, extracellular vesicles (EVs) could also attenuate the potential risk of genetic engineering and pave the way towards the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their anti-inflammatory and vascular-support effects, the homing ability of MSCs supplements their paracrine function, and is involved in protecting microvessel density ( 32 ). Transplanted MSCs detect signals from injured kidney cells and are chemoattracted to the damaged site ( 33 ). During AKI, endothelial cells express high levels of tumor necrosis factor (TNF) and interleukins (ILs), which can up-regulate the β subunit of very late antigen-4 and vascular adhesion molecule 1 to mediate the effect of bone marrow MSCs on endothelial cell adhesion ( 33 ).…”
Section: Mechanisms Of Msc Therapy In Akimentioning
confidence: 99%
“…Transplanted MSCs detect signals from injured kidney cells and are chemoattracted to the damaged site ( 33 ). During AKI, endothelial cells express high levels of tumor necrosis factor (TNF) and interleukins (ILs), which can up-regulate the β subunit of very late antigen-4 and vascular adhesion molecule 1 to mediate the effect of bone marrow MSCs on endothelial cell adhesion ( 33 ). CXC motif chemokine receptor 4 (CXCR4) is a specific receptor for chemokine stromal cell-derived factor-1 (CXCL12), and CXCR4 cells are responsible for the renal repair function in AKI ( 34 ).…”
Section: Mechanisms Of Msc Therapy In Akimentioning
confidence: 99%